Increased Mobile Zinc Regulates Retinal Ganglion Cell Survival via Activating Mitochondrial OMA1 and Integrated Stress Response - Jiahui Tang; Zhe Liu; Jiaxu Han; Jingfei Xue; Liyan Liu; Jicheng Lin; Caiqing Wu; Qi Zhang; Siting Wu; Canying Liu; Haishun Huang; Yuanyuan Fu; et al. (MDPI AG, 2022)
Retinal ganglion cells (RGCs), the projection neurons of the eye, are irreversibly lost once the optic nerve is injured, which is a critical mechanism of glaucoma. Mobile zinc (Zn2+) levels rapidly increase in retinal interneuron amacrine cells and Zn2+ is then transferred to RGCs via the Zn2+ transporter protein ZnT-3, triggering RGC loss in optic nerve injury. Zn2+ chelation and ZnT-3 deletion promote long-term RGC survival. However, the downstream signaling pathways of Zn2+ in RGCs remains unknown. Here, we show that increased levels of Zn2+ upregulate the expression and activity of mitochondrial zinc metallopeptidase OMA1 in the retina, leading to the cleavage of DELE1 and activation of cytosolic eIF2α kinase PKR, triggering the integrated stress response (ISR) in RGCs. Our study identified OMA1 and ISR as the downstream molecular mechanisms of retinal Zn2+ and potential targets for preventing the progression of Zn2+-associated neuronal damage.